Empoderamento econômico das mulheres de São Vicente através do microcrédito - Santos, Eliane Sueli da Luz dos (2013)
Women and children are the most affected by the effects of poverty, social inequality and gender, and the woman always seeks an alternative to produce additional income to ensure the sustenance of the family and balance in family income. Microfinance emerged as an important aid to these women, barred from recourse to traditional forms of credit, turn to institutions that provide microfinance to perform professionally and increase family income by changing this image of women dependent on men, becoming stronger and more autonomous, but keeping its essence of Cape Verdean woman of mother and head of household. The present work aims to demonstrate the contribution of microcredit offered by MORABI for the economic empowerment of women on the island of São Vicente - Cape Verde, also assuming an important tool for combating poverty and social exclusion in the country. This is a survey conducted through questionnaires administered by telephone and by personal interview scheduled. As for research purposes is classified as exploratory and descriptive and the means as telematic, literature and documents. After the analysis of the dice it is concluded that microcredit contributes to the economic empowerment of women of São Vicente, many received micro-credit more than once, expanding the business, ensuring not only self-employment, but also the third job, developing the community where they live. After having applied the microcredit most claimed to be feeling more independent and satisfied, and thus raise their self-esteem, improve the living conditions of their families to health, food, housing (many have managed to increase the number of rooms of the House) and in education, where it is worth noting that many are able to pay the University of children both in the country and abroad.